Uma conjuntura de aparências: a não construção de um sistema municipal de planejamento urbano em Ouro Preto - Ricardo dos Santos Teixeira (2015)
Icon in the history of Brazil and one of the most important Baroque collections in the world, the city of Ouro Preto was declared National Monument in 1933; declared national heritage in 1938; and recognized as a World Heritage Site by UNESCO in 1980. Even figuringas an expressive exemplary in Brazilian artistic and architectural production, Ouro Preto also is a portrait of urban problems experienced by other municipalities of the same size, having gone through phases of decay and disordered urban sprawl. Over the years, there have beenvarious attempts to implement urban planning in Ouro Preto. They all represent a reading of the time that municipality lived, as well as the paths taken by the Urban Planning and the Heritage Preservation in Brazil. In this perspective, this thesis proposed the analysis of "urbanplans" and urban planning legislation of Ouro Preto, to evaluate the trajectory of the construction of the municipal urban planning system, facing advances and limitations of several elaborated proposals for the municipality, from the second half of the twentieth century to the present. History of urban planning in Ouro Preto shows remarkable convergences with its history in Brazil, making it possible, based on the object of study, revisit, even in part, the history of urban planning in Brazil, in their various formats, concepts and ideologies. This revisit reinforces the need to consolidate a culture of planning in Ouro Preto, which can be extendedto several other municipalities, and that it is a paradigm shift, important to change the course of Brazilian municipalities, yet rooted in a conjuncture of appearances whose master plans hide the lack of urban planning.